Inventory Distribution and potential of the type Macaranga Spp Forest IUPHHK PT. Ratah Timber in the village Mamahak Teboq District of Long Hubung Mahakam Ulu Regency of East Kalimantan - Kukumeo, Yanuardus Edmond; Tirkaamiana, Taufan; Kamarubayana, Legowo (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The purpose  of  this study was to determine the types of trees at the potential and deployment  Macaranga Spp haul roads around  wood PT. Ratah Timber particularly at Km  23.26 and 30 villages  Mamahak  Teboq  District of  Long Hubung Mahakam  Ulu Regency. Data collection  and research done by the preparation method of  sampling  is  done  using  a 20x20 meter plots  were arranged in lines of research.  Number of PU in daloam each path varies according to the field conditions, distance of between 9-10 plots.Also in  the   interview  did also  used to obtain  data and information from officers in the field, officials of relevant agencies and  the  local population  that  has  to do with the  activities  of research and from the literature that support.Research results can be sorted by diameter class is 10-15, 16-20, 21-30, and> 30 cm  and are obtained  1) Volume  Macaranga Spp tree on plot  1, 2 and 3 with a diameter  of  10-15 cm  class is 10 , 58 m³ with 236 trees, the diameter  class 16-20 cm  was 6.35 m³ there  are 62 trees,  while the volume with a diameter of 21-30 cm class is 15.64 m³ there  are 75 trees  while the number  of  overall diameter  is  32.97  m³.  Distribution  Macaranga Spp  tree   most commonly found on the second plot  with 173 trees  including the number of trees under 10 cm  in diameter (not measured).Suggestions submitted on the results of  this study are 1) To    the   PT.  Ratah   Timber   trying   keep  the   existence  and preservation  of   trees   Macaranga  Spp.  existing   in  PT.  Ratah Timber from forest fires disorders; 2) Keep an inventory of  trees Macaranga  Spp.  on  the   whole  area   of   PT.  Ratah  Timber  to determine the distribution and potential Macaranga Spp.